Influence of time-of-day on neuromuscular performance in team sport athletes: a systematic review and meta-analysis - Martin-López, J.; Pérez-López, A.; Varillas-Delgado, D.; López-Samanes, Á. (Frontiers in Sports and Active Living, 2025)
Introduction: Although circadian rhythms have been shown to influence some neuromuscular performance tasks, the time-of-day effect on team sports performance athletes remains equivocal. This study aimed to examine the existing evidence concerning diurnal variations in neuromuscular performance in professional and semi-professional team sports athletes using a meta-analytic approach.